2020
DOI: 10.1108/er-11-2019-0446
|View full text |Cite
|
Sign up to set email alerts
|

Productivity or illusion? Assessing employees' behavior in an employability paradox

Abstract: PurposeEmployability has been studied in different disciplines (e.g. occupational health and career) and has been seen as a personal resource with overall positive outcomes. The present research investigates the behavioral implications of (perceived) employability and responds to the recent call of research that perceived employability could have not only positive but also negative behavioral implications. Furthermore, this study aims to reduce the asymmetry of data set and replication of existing results in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 98 publications
3
23
0
Order By: Relevance
“…Another aspect is that our model focuses on individual creativity, and testing the same model at team level could be helpful in understanding the role of authentic leaders in teams (Hoch et al, 2018). Though data collected from the same source either in one or different time are being used in behavioral and leadership studies, causal influences cannot be treated as conclusive (Imam and Chambel, 2020;Xu et al, 2017). Even though we accounted for the common method variance in our dataset, common method bias may still exist.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Another aspect is that our model focuses on individual creativity, and testing the same model at team level could be helpful in understanding the role of authentic leaders in teams (Hoch et al, 2018). Though data collected from the same source either in one or different time are being used in behavioral and leadership studies, causal influences cannot be treated as conclusive (Imam and Chambel, 2020;Xu et al, 2017). Even though we accounted for the common method variance in our dataset, common method bias may still exist.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Moreover, by employing the dynamics of the vocational behavior paradigm within the framework of career construction theory (Cwr et al, 2019), we identify a behavioral mediator-problem-based learning-linking the relationship between students' future orientation and their perceived employability. By opening the black box of the influence of future orientation on employability, we thus not only provide empirical findings that enrich the use of career construction theory in the employability literature (Forrier et al, 2015) but also underscore the empirical importance of the behavioral perspective for such research (Imam & Chambel, 2020).…”
Section: Practical Implicationsmentioning
confidence: 75%
“…In the future, a perceived employability-actual turnover behavior based paradox should be adopted (Nelissen et al, 2017), with a cross cultural perspective suggested by Wong and Cheng (2020). Sixth, including this study, empirical findings on employability paradox were all limited in single-level significant models so far (see De Cuyper et al, 2011a;De Cuyper and De Witte, 2011;Acikgoz et al, 2016;De Vos et al, 2017;Nelissen et al, 2017;Imam and Chambel, 2020;Rodrigues et al, 2020). In the future, researchers could take high level factors into account, such as organization and team, to formulate a multilevel structure model of employability paradox.…”
Section: Limitations and Future Extensionsmentioning
confidence: 90%
“…The paradox of employability refers to the fact that improved employability can bring both positive impacts and negative risks to the organization (De Grip et al, 2004). The positive impact usually refers to improvement in employees' performance and organizational behaviors, whereas the negative impact is reflected in increased turnover intention, job search intensity and counterproductive work behaviors or reduced emotional organizational commitment (De Cuyper et al, 2011a;De Cuyper and De Witte, 2011;Acikgoz et al, 2016;De Vos et al, 2017;Nelissen et al, 2017;Imam and Chambel, 2020;Rodrigues et al, 2020). In this study, we focus on the paradox that improvement in perceived employability brings about the increase in both performance and turnover intention.…”
Section: Employability and Employability Paradoxmentioning
confidence: 99%
See 1 more Smart Citation